DAMPAK PANDEMI COVID-19 TERHADAP EKONOMI DAN LINGKUNGAN FISIK DI DESA WISATA DI BALI - Dewa Ayu Made Lily Dianasari (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The COVID-19 pandemic had a very significant impact on tourism in Bali, as evidenced by decreasing tourist visits to Bali. The decline of tourist visits had an impact on the economy and the physical environment in Bali, especially in Tourism Villages. The survey was conducted on the local communities involved in the management of tourist villages in Bali as many as 100 respondents to get the community's perception of the impact given to the economy and the physical environment during the COVID-19 pandemic. The sampling technique used was purposive sampling and quota sampling then analyzed by using confirmatory factor analysis. Community perceptions in tourist villages in Bali about the impact of the COVID-19 pandemic on the economy have a negative impact. This can be seen from the highest average value which has the highest loading factor matrix value of 0,773. The perception of communities in tourist villages in Bali about the impact of Covid-19 on the environment tends to have a positive impact. This can be seen from the results of the highest loading factor value in a positive statement with a value of 0,868; that is cleaner water conditions in the tourism village.